Unexpected thymoma in a challenging case of hyperparathyroidism - Federico Raveglia; Loredana De Pasquale; Ugo Cioffi; Giorgio Ghilardi; Matilde De Simone; Monica Falleni; Alessandro Baisi (Clinical Case Reports, 2020)
Abstract We report the case of a woman with primary hyperparathyroidism suspected of mediastinal ectopic parathyroid adenoma revealed to be a thymoma. Our aim was to focus on some possible criticisms in distinguishing between ectopic parathyroid and thymus.